Unveiling Corporate Social Responsibility in Philippine Microfinance Institutions: A Proposed Assessment Guidelines and Enhancement Activities - Kevin M Rivera (Journal of Social Entrepreneurship Theory and Practice, 2023)
While sustainable communities are at the forefront of Microfinance Institutions (MFIs) objectives worldwide, a discernible inclination towards profit-seeking persists. This study presents an opportunity to refine MFIs' CSR-related activities and bolster community awareness of their unwavering commitment to Corporate Social Responsibility (CSR). Specifically, this research used proportional stratified random sampling for the employees and clients of ten microfinance institutions (MFIs) in the Philippines. However, due to the massive number of clients of MFIs, incidental sampling was considered and used in gathering data from the clients of the microfinance institutions. Employing descriptive design and t-test, the research unveils MFIs' primary focus on health programs, charitable works, youth and sports development, disaster and relief operations, and environmental sustainability. These compelling findings serve as a dependable foundation for the establishment of CSR assessment guidelines, empowering MFIs to propel community-driven sustainable development. Embracing targeted CSR efforts, MFIs can catalyze transformative change, nurturing resilient and thriving communities.